Surface Treatment Technologies for Wear Resistance Increasing of 42CrMo4 Steel - Doan, Van Thanh; Kusmic, David; Pospichal, Miroslav (Manufacturing Technology Journal, 2015)
The present study was directed to investigate the mechanical and tribological properties of 42CrMo4 (CSN 41 5142.3) steel, which was thermochemical treated by the technologies of tenifer, manganese phosphate and plasma nitriding combining with blackening. Plasma nitriding was carried out for the samples under different condition of gas mixture under temperature of 480C (plasma sputtering) and 500C (plasma nitriding process) for 10h. Besides determining the microhardness (HV 0.05), surface hardness, and microstructure, this paper also concentrates on the field of wear resistance evaluation and friction coefficient of these surface treatments. Based on ``ball on flat'' test, calotest, and profile observation, it was found that tenifer technology is suitable to increase the wear resistance, and manganese phosphate improves clearly not only wear resistance but also friction coefficient, which can be usable for weapon production.
Keywords: Wear resistance; Friction coefficient; Plasma nitriding; Tenifer; Manganese Phosphate